Auditory assessment of children with severe hearing loss using behavioural observation audiometry and brainstem evoked response audiometry - Kumari, Rakhi; Chakraborty, Priyanko; Jain, R. K.; Kumar, Dhananjay (International Journal of Research in Medical Sciences, 2017)
Background:Early detection of hearing loss has been a long-standing priority in the field of audiology. Currently available auditory testing methods include both behavioural and non-behavioural or objective tests of hearing. This study was planned with an objective to assess hearing loss in children using behavioural observation audiometry and brain stem evoked response audiometry. Methods: A total of 105 cases suffering from severe to profound hearing loss were registered. After proper history and clinical examination patients were subjected to behavioural observation audiometry (BOA) and brainstem evoked response audiometry test (BERA). Results: Out of 105 cases in 62 cases (59.05%) the findings of both BOA and BERA tests were similar but in 43 cases the findings of both tests were not similar. In total 18 cases (17.14%) diagnosis of severe hearing loss could be made by BERA test only because of in 10 cases there was inconclusive BOA finding and in 8 cases there was no response in BOA test. Conclusions: Behavioural observation audiometry can detect hearing loss but in developmentally retardrd children in whom responses are difficult to elicited, this test is not so conclusive. BERA is the tool which can confirm the normal sensitivity of hearing in such persons whenever required and is very useful in early detection of hearing loss and planning rehabilitative procedures.